Herpesviral microRNAs in Cellular Metabolism and Immune Responses - Kim, Hyoji; Iizasa, Hisashi; Kanehiro, Yuichi; Fekadu, Sintayehu; Yoshiyama, Hironori (Frontiers in Microbiology, 2017)
The microRNAs (miRNAs) function as a key regulator in many biological processes through post-transcriptional suppression of messenger RNAs. Recent advancements have revealed that miRNAs are involved in many biological functions of cells. Not only host cells but also some viruses encode miRNAs in their genomes. Viral miRNAs regulate cell proliferation, differentiation, apoptosis, and the cell cycle to establish infection and produce viral progeny. Particularly, miRNAs encoded by herpes virus families play integral roles in persistent viral infection either by regulation of metabolic processes or the immune response of host cells. The life-long persistent infection of gamma herpes virus subfamilies, such as Epstein-Barr virus and Kaposi’s sarcoma-associated herpesvirus, induces host cells to malignant transformation. The unbalanced metabolic processes and evasion from host immune surveillance by viral miRNAs are induced either by direct targeting of key proteins or indirect regulation of multiple signaling pathways. We provide an overview of the pathogenic roles of viral miRNAs in cellular metabolism and immune responses during herpesvirus infection.